Manajemen Sumber Dana dan Alokasi Pembiayaan Pada Pesantren Mahasiswa - Andhika Sakti; Ara Hidayat (UIN Sunan Gunung Djati Bandung, 2019)
This study aims to find out how the management of financing management in Islamic boarding school students Ma’had Lughowy. The focus of this investigation is to reveal where Ma'had Lughowy's funding sources are, how Ma'had Lughowy's funding allocations are and how student-based boarding schools carry out their activities. The method used in this research is the cost-benefit analysis (CBA) method presented by descriptive analysis with a qualitative approach. The results of the investigation show that there is still a management of financing that is not in accordance with the concept of management in general in Ma'had Lughowy. (2) in its implementation, ma'had needs an average operational cost budget of Rp. 10,000,000.00 to Rp. 15,000,000.00 every month and to meet the needs of students who are quite a lot of managers using a strategy of 100% of the income of 20% saved for savings funds and another 80% is managed for a budget for one year. (3) Ma'had Lughawy still has an existence up to now due to several factors, among others, because ma'had has become a necessity for students, as a means that is intentionally formed to equalize students' academic abilities, to be a solution for housing choices with a good environment for students and as one of the graduation requirements. Therefore it is necessary to have a good strategy in managing the sources and allocation of funds in accordance with the management concepts that exist in student boarding schools.